Data commons - Gijs van Maanen; Charlotte Ducuing; Tommaso Fia (Internet Policy Review, 2024)
Data commons is an often-used but also ambiguous notion, and aspires to connect the complex notion of ‘data’ with that of the ‘commons’ — a concept with an equally variable and contested meaning. This entry collects and connects several recent contributions to discussions on data commons as a means to foreground several important community-related themes. We take this discursive move to be important because the adjective ‘data’ has the tendency to transform social, communal, and political problems into technological ones that result in confusions between means and ends that endanger the viability of the commons. We discuss four themes that help to re-prioritise community-related interests and problems over their technological solutions. We discuss a data commons relationship to itself (1), its relationship to other commons (2), to capitalism (3), and sustainability (4). We structure the literature on data commons to contextualise, historicise, and politicise data commons, and ultimately understand them as ways of living together (with data) rather than as instruments to manage data.